2021
DOI: 10.1158/0008-5472.can-21-1337
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 Activity in Tumor-Initiating Cells Remodels Myeloid-Derived Suppressor Cells to Promote Breast Cancer Progression

Abstract: Tumor-initiating cells (TIC) are associated with tumor initiation, growth, metastasis, and recurrence. Aldehyde dehydrogenase 1A1 (ALDH1A1) is a TIC marker in many cancers, including breast cancer. However, the molecular mechanisms underlying ALDH1A1 functions in solid tumors remain largely unknown. Here we demonstrate that ALDH1A1 enzymatic activity facilitates breast tumor growth. Mechanistically, ALDH1A1 decreased the intracellular pH in breast cancer cells to promote phosphorylation of TAK1, activate NFκB … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Liu et al made a breakthrough in research regarding the mechanism by which ALDH1A1 initiates breast cancer. They found that ALDH1A1 decreased the intracellular pH in breast cancer cells, in order to promote the phosphorylation of TAK1, activate the NFkB signal pathway, and increase the secretion of GM-CSF, and this led to myeloidderived suppressor cell expansion and immunosuppression (89).…”
Section: The Regulatory Mechanism Of Aldh1a1 In Cancers Is Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al made a breakthrough in research regarding the mechanism by which ALDH1A1 initiates breast cancer. They found that ALDH1A1 decreased the intracellular pH in breast cancer cells, in order to promote the phosphorylation of TAK1, activate the NFkB signal pathway, and increase the secretion of GM-CSF, and this led to myeloidderived suppressor cell expansion and immunosuppression (89).…”
Section: The Regulatory Mechanism Of Aldh1a1 In Cancers Is Complexmentioning
confidence: 99%
“…reported that NCT-501, an ALDH1A1 selective inhibitor, could augment the efficacy of olaparib during ovarian cancer treatment ( 86 ). Another group of researchers reported that the ALDH1A1 inhibitor disulfiram and chemotherapeutic agent gemcitabine cooperatively inhibited breast tumor growth and tumorigenesis by purging ALDH+ tumor-initiating cells and activating T-cell immunity ( 89 ). Recently, benzimidazole derivatives have been found to act as potent and selective ALDH1A1 inhibitors ( 8 ).…”
Section: Aldh1a1 Can Be Seen As a Therapeutic Target For Cancersmentioning
confidence: 99%
“…Disulfiram inhibits human lens ALDH1A1 at IC50 values of the micromolar range [59]. In breast cancer cells, ALDH1A1 enzymatic activity facilitated breast tumor growth, and acidified the cytosol to promote phosphorylation of TAK1, activate NFκB signaling, and to increase the secretion of granulocyte macrophage colony-stimulating factor (GM-CSF), which led to myeloid-derived suppressor cell (MDSC) expansion and immunosuppression; disulfiram and chemotherapeutic agent gemcitabine cooperatively inhibited breast tumor growth and tumorigenesis by purging ALDH+ cancer stem cells, and by activating T cell immunity [141].…”
Section: Inhibition Of Aldh As a Potential Therapeutic Approachmentioning
confidence: 99%
“…In addition, gemcitabine can prevent RNA synthesis, which reasonably explains its cytotoxicity [ 12 ]. Relevant studies and systematic reviews have also confirmed the efficacy of gemcitabine in other malignant tumors [ 13 , 14 ]. As is known to all, the PF is one of the primary options for the treatment of metastatic NPC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%